LABOUR RIGHTS PROTECTION FOR YOUNG WORKERS ON DIGITAL LABOUR PLATFORMS: AN ISLAMIC PERSPECTIVE - Siti Suraya Abd Razak; Harlida Abdul Wahab; Roshazlizawati Mohd Nor; Teh Zaharah Yaacob (Malaysian Journal of Syariah and Law)
The development of digital labour platform resulted from the growth of digital economy and has transformed the world of work. However, the progress of platforms has stagnated due to various issues arising in the employment relationship between platform providers and young workers. These issues include wages, compensation and benefits, working hours, rest days, leave and public holidays. Young workers often face unfair treatment by platform providers while performing their tasks. The research objectives of this study are twofold: firstly, to analyse the labour rights of workers from an Islamic perspective and secondly, to explore how the labour rights of young workers on digital labour platforms can be improved through Islamic principles. A qualitative method is employed to achieve these objectives. The content analysis method is used to analyse secondary sources relevant to this study. The main sources of this research are the Qur’an, hadith and journal articles. Additionally, the Employment Act 1955 (Act 265) and the Children and Young Persons Employment Act 1996 (Act 350) are also analysed to reach the objectives of this study. The findings of this study show that Islam promotes justice in the employment relationship between employer and employee. Consequently, existing legislation must be improved to ensure labour protection for young workers on digital labour platforms. This study contributes to the theoretical framework of labour rights by expanding the discussion to include digital labour platforms and young workers. Furthermore, it explores the Islamic perspective on labour rights for young workers on digital labour platforms.